Research on the Application of Plasma Welding Technology in Sealing Welding of Railway Vehicle - WANG Fu - quan, WANG Su - huan, LI Gang - qing, DING Ming - fei (Cailiao Baohu, 2022)
In order to explore the application of plasma welding technology with heat concentration and small deformation in railway transit vehicles, so as to realize the sealing welding of trunk line stainless steel car body, the appearance, structure and mechanical properties of four kinds of sealing weld joints of a prepared certain vehicle type were studied by optimizing welding current, welding voltage, plasma gas flow and other test parameters. Results showed that for four typical joints, the welds with good surface formation, uniform and continuous weld bead without undercut, porosity, inclusion, lack of fusion, lack of penetration and other defects could be obtained under the determined welding process parameters respectively. The microstructure of joint weld area was composed of austenitic column crystal, and a small amount of point - shaped δ - ferrite grains were precipitated between the grains. The mechanical strengths of the joints were far higher than the standard requirements, which met the technical requirements of stainless steel welded joints for railway rolling properties.